Komunikasi Politik Islam di Indonesia: Tinjauan Literatur Sistematis Wacana Publik Mahfud MD - Dalimunthe , Ambali (PT Anugerah Literasi Indomedia, 2025)
This study analyzes the construction of Mahfud MD's thinking on the relationship between Islam and the state in the context of increasing political polarization and identity populism in Indonesia. In recent years, public debates have often been characterized by the manipulation of religious symbols and the narrowing of the meaning of Islam, so there is a need for studies that can explain how intellectual-state actors respond to these dynamics. This study uses the Systematic Literature Review (SLR) method which collects journal articles, academic books, public documents, and speeches by Mahfud MD to identify the argumentation patterns and theoretical frameworks used in his discourse. The results of the study show that Mahfud MD combines the principles of wasathiyah (moderation), maqāṣid al-syarī'ah, and modern constitutionalism to affirm Islam as an inclusive public ethics, not an instrument of electoral mobilization. He dismantles the logic of populism through criticism of verse manipulation, identity abuse, and narrowing of religious interpretations, as well as encouraging public rationality through legal literacy and civic ethics. The discussion emphasized that this approach produces a constitutional Islamic model that is relevant for strengthening democracy and the stability of the public space. This research contributes to expanding the study of Islamic moderation by emphasizing the importance of integrating religious values and the framework of the state of law. Penelitian ini menganalisis konstruksi pemikiran Mahfud MD mengenai hubungan Islam dan negara dalam konteks meningkatnya polarisasi politik dan populisme identitas di Indonesia. Dalam beberapa tahun terakhir, perdebatan publik kerap ditandai oleh manipulasi simbol keagamaan dan penyempitan makna Islam, sehingga diperlukan kajian yang mampu menjelaskan bagaimana aktor intelektual-negara merespons dinamika tersebut. Penelitian ini menggunakan metode Systematic Literature Review (SLR) yang menghimpun artikel jurnal, buku akademik, dokumen publik, serta pidato Mahfud MD untuk mengidentifikasi pola argumentasi dan kerangka teoretis yang digunakan dalam wacananya. Hasil penelitian menunjukkan bahwa Mahfud MD memadukan prinsip wasathiyah (moderasi), maqāṣid al-syarī‘ah, dan konstitusionalisme modern untuk menegaskan Islam sebagai etika publik yang inklusif, bukan instrumen mobilisasi elektoral. Ia membongkar logika populisme melalui kritik terhadap manipulasi ayat, penyalahgunaan identitas, dan penyempitan tafsir keagamaan, serta mendorong rasionalitas publik melalui literasi hukum dan etika kewargaan. Pembahasan menegaskan bahwa pendekatan ini menghasilkan model Islam konstitusional yang relevan bagi penguatan demokrasi dan stabilitas ruang publik. Penelitian ini berkontribusi dalam memperluas kajian moderasi Islam dengan menekankan pentingnya integrasi nilai agama dan kerangka negara hukum.